Sclerotherapy for Venous Malformations of the Pharynx or the Tongue Base Without Tracheostomy: Treatment Protocol With Intubation and Outcomes. Issue 3 (May 2020) - Iwashina, Yuki; Ozaki, Mine; Wong, Manzhi; Ihara, Aki; Fujiki, Masahide; Takushima, Akihiko; Harii, Kiyonori
Abstract : Abstract: Venous malformations (VMs) occurring in the tongue base or pharynx are rare, but can cause airway obstruction. Considering the potential issues or morbidity related to surgical resection in the tongue or pharynx region, sclerotherapy is often preferred. We perform sclerotherapy for such lesions without conducting tracheotomy, but keep patients intubated for a certain period. Outcomes of sclerotherapy, and benefits and cautions related with our protocol were investigated. Our subjects were 10 cases in 9 patients who underwent sclerotherapy for VMs of the tongue base (6 patients) or pharynx (3 patients) from 2008 to 2017. One patient underwent treatment sessions twice. The sclerosants used were absolute ethanol (ET) (3 cases), 5% ethanolamine oleate (EO) (4 cases), or both ET and 5%EO (3 cases). In 5 of 9 patients, postoperative MRI was performed, which revealed lesion volume reduction by 12% to 47%. The intubation period varied according to the sclerosant used: ET, 5 to 11 days; 5% EO, 2 to 12 days; and combination of ET and 5% EO, 8 days. Postoperative complications included fever of unknown (n = 2), acute psychosis (n = 3), vocal cord paralysis (n = 2), and bradycardia induced from the use of a sedative agent (n = 1). One patient complained of mild transient swallowing difficulty that lasted for a month postoperatively. Although our method mandatorily requires careful postoperative management in an ICU, including sedation with anesthetic agents and artificial respiration by intubation for a certain period of time, no serious complications or post-therapeutic morbidities occurred. Abstract : Supplemental Digital Content is available in the text